Caracterização da vegetação secundária do bioma mata atlântica com base em sua posição na paisagem - Ferreira Marmontel, Caio Vinicius [UNESP]; Rodrigues, Valdemir Antonio [UNESP]; Martins e Martins, Thiago [UNESP]; Starzynski, Roberto; Carvalho, Jose Luiz de (Univ Federal Uberlandia, 2013)
This study characterized the Atlantic Forest vegetation and compared the structure of the native tree community occurring along a toposequence at watershed D of the Serra do Mar State Park, municipality of Cunha, SP - Brazil. The study was conducted in 64 plots, of 10 x 10 m, distributed in sites downstream (T1), intermediate (T2) and upstream (T3) of the toposequence, recording all individuals with DBH (Diameter at Breast Height) >= 0.5 cm. Altogether 1.093 individuals were sampled, and 89 species were identified, belonging to 61 genders and 31 families. At T1 site there was a greater abundance and density of individuals; T2 had the highest diversity index and basal area; while in T3 it was observed highest species richness and greater percentage of rare species. The specie Cyathea delgadii in the lower third of toposequence, and the Alchornea triplinervea in the intermediate and upper third were the most important. The sites downstream and upstream of the toposequence showed the largest differences in structure. In the middle portion of the watershed and there was a greater difference between the similarity between species.

Este trabalho teve como objetivo caracterizar a vegetação de Mata Atlântica e comparar a estrutura da comunidade arbórea nativa que ocorre na toposequência da microbacia “D” do Parque Estadual Serra do Mar, município de Cunha, SP - Brasil. O estudo foi realizado em 64 parcelas de 10 x 10 m, distribuídas na jusante (T1), intermediária (T2) e montante (T3) da toposequência, nas quais foram identificados botanicamente todos os indivíduos com DAP (diâmetro a altura do peito) > 0,5 cm. No conjunto 1.093 indivíduos foram amostrados, inclusas em 89 espécies, 61 gêneros e 31 famílias. Na T1 constatou-se maior abundância e densidade de indivíduos, a T2 teve maior índice de diversidade e área basal, enquanto na T3 foi observada maior riqueza de espécies e maior porcentagem de espécies raras. A espécie Cyathea delgadii no terço inferior da toposequencia e a Alchornea triplinervea na intermediária e terço superior foram as que apresentaram maior índice de valor de importância. Nas seções a jusante e montante da toposequência ocorreram as maiores diferenças em termos de estrutura. Na parte intermediária e na montante da microbacia houve maior diferença entre a similaridade entre espécies.
Characterization of vegetation of secondary of biome atlantic forest com base on your position in the landscape
Keywords: Diversity; Native species; Watershed; Similarity